(untitled) (Journal of Fiber Bioengineering and Informatics, 2020)
Limited availablilty of personal protective equipment (PPE) during the current COVID-19 pandemic has led to frequent unsafe reuse of personal protective clothing by healthcare workers and the public. The application of ozone gas to sterilize PPEs for reuse has been proposed. However, the potential damage inflicted on the fabrics has not been reported in the scientific literature. A study was conducted to investigate the changes in fabric elasticity that may be associated with a two-hour exposure to ozone gas at a concentration of 17 ppm. No significant material degradation was found. The results suggest that use of ozone gas to sterilize PPEs for reuse against COVID-19 virus can be effective.